The Role of Gut Microbiota and Microbiota-Related Serum Metabolites in the Progression of Diabetic Kidney Disease - Zhang, Qing; Zhang, Yanmei; Zeng, Lu; Chen, Guowei; Zhang, La; Liu, Meifang; Sheng, Hongqin; Hu, Xiaoxuan; Su, Jingxu; Zhang, Duo; Lu, Fuhua; Liu, Xusheng; et al. (Frontiers in Pharmacology, 2021)
Objective Diabetic kidney disease (DKD) has become the major cause of the end-stage renal disease (ESRD) associated with the progression of renal fibrosis. As gut microbiota dysbiosis is closely related to renal damage and fibrosis, we investigated the role of gut microbiota and microbiota-related serum metabolites in DKD progression in this study. Methods Fecal and serum samples obtained from pre-dialysis DKD patients from January 2017 to December 2019 were detected using 16S rRNA gene sequencing and liquid chromatography-mass spectrometer respectively. Forty-one pre-dialysis patients were divided into two groups according to their estimated glomerular filtration rate (eGFR): the DKD non-ESRD group (eGFR≥15ml/min/1.73m2) (n=22), and the DKD ESRD group (eGFR<15ml/min/1.73m2) (n=19). The metabolic pathways related to differential serum metabolites were obtained by KEGG pathway analysis. Differences between the two groups relative to gut microbiota profiles and serum metabolites were investigated, and associations between gut microbiota and metabolite concentrations were assessed. Correlations between clinical indicators and both microbiota-related metabolites and gut microbiota were calculated by Spearman rank correlation coefficient and visualized by heatmap. Results Eleven different intestinal floras and 239 different serum metabolites were identified between the two groups. Of 239 serum metabolites, 192 related to the eleven different intestinal flora were mainly enriched in six metabolic pathways, among which, phenylalanine and tryptophan metabolic pathways were most associated with DKD progression. Four microbiota-related metabolites in the phenylalanine metabolic pathway (hippuric acid (HA), L- (-)- 3-phenylactic acid, trans-3-hydroxy-cinnamate, and dihydro-3-coumaric acid), and indole-3 acetic acid (IAA) in the tryptophan metabolic pathway positively correlated with DKD progression, whereas L-tryptophan in the tryptophan metabolic pathway had a negative correlation. Intestinal flora g_Abiotrophia and g_norank_f_Peptococcaceae were positively correlated with the increase of renal function indicators and serum metabolite HA. G_Lachnospiraceae_NC2004_Group was negatively correlated with the increase of renal function indicators, and serum metabolites (L-(-)-3-Phenyllactic acid and IAA). Conclusions This study highlights the interaction among gut microbiota, serum metabolites, and clinical indicators in pre-dialysis DKD patients, and provides new insights into the role of gut microbiota and microbiota-related serum metabolites that were enriched in the phenylalanine and tryptophan metabolic pathways which correlated with the progression of DKD.